GEMBANGAN GAME SCI-FI BERBASIS NOVEL DENGAN GAYA PIXEL ART - Perdana, Firmanda Adi; Anshori, Iedam Fardian (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
This research focuses on the development of a science fiction game based on the novel "Distorsi" written by the researcher. Unreal Engine is used as the primary platform, with pixel art style as the main visual element. The research aims to bring the novel's story into an interactive gaming experience. The use of Unreal Engine enables in-depth development. The pixel art style was chosen to create a unique retro touch. The research encompasses character design, environment creation, and the implementation of narrative elements within Unreal Engine. The result is a game that combines the novel's story with engaging gameplay challenges, all within the pixel art aesthetic. Throughout the research, obstacles and lessons encountered are discussed, as well as the impact of art and story on the player's experience